الصلاح الديني والسلوك الاجتماعي في المجتمع الإندونيسي؛ ظاهرة الانفصام ومنهج للتقريب - M. Kholid Muslih (Tsaqofah, 2021)
This article aims to observe the phenomenon of individual piety in religion in Indonesia Indonesian society, which according to research results, has grown significantly over time, and it affects their social and political behavior, which he says there is no relation between the two. This study uses a descriptive analysis approach, with the conclusion: that individual piety in religion has a major influence on the formation of social goodness and politics, and vice versa. What is said that the growth of the phenomenon of piety individuals in religion does not affect the progress of Islamist-oriented parties Nationalists in getting the vote of voters is not right, because most of the voters for Nationalist Islamist oriented parties they are religious. It means, that the progress of the parties requires more effort in expanding the circle individual piety in religion, on the one hand, and presenting different approaches good humanity to attract voices from non-religious circles on the other side.